2016
DOI: 10.1144/sp445.11
|View full text |Cite
|
Sign up to set email alerts
|

Investigations of continued reservoir triggered seismicity at Koyna, India

Abstract: Koyna, located in the Deccan Volcanic Province in western India, is the most significant site of reservoir triggered seismicity (RTS) globally. The largest RTS event of M 6.3 occurred here on December 10, 1967. RTS at Koyna has continued. This includes 22 M≥5.0 and thousands of smaller events over the past 50 years. The annual loading and unloading cycles of the Koyna Reservoir and the nearby Warna Reservoir influence RTS. Koyna provides an excellent natural laboratory to comprehend the mechanism of RTS becaus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(20 citation statements)
references
References 60 publications
2
16
0
Order By: Relevance
“…The Koyna region, situated in western India, is a wellknown site of reservoir-triggered seismicity (RTS), where triggered earthquakes have been occurring in a restricted area of 30 × 20 km 2 since the impoundment of the Koyna reservoir in 1962 [27][28][29][30][31][32][33][34]. There were no earthquakes reported in the Koyna region prior to impoundment of the reservoir within 50 km of the Koyna dam, but the seismic activity started in the months following the impoundment and increased gradually during the next few years culminating in the M~6.3 Koyna earthquake of December 10, 1967 [29,35].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Koyna region, situated in western India, is a wellknown site of reservoir-triggered seismicity (RTS), where triggered earthquakes have been occurring in a restricted area of 30 × 20 km 2 since the impoundment of the Koyna reservoir in 1962 [27][28][29][30][31][32][33][34]. There were no earthquakes reported in the Koyna region prior to impoundment of the reservoir within 50 km of the Koyna dam, but the seismic activity started in the months following the impoundment and increased gradually during the next few years culminating in the M~6.3 Koyna earthquake of December 10, 1967 [29,35].…”
Section: Introductionmentioning
confidence: 99%
“…The region continues to be active with recurrent, low magnitude earthquakes. A strong correlation between earthquake occurrences and the annual loading and unloading cycles of the Koyna and Warna reservoirs has been established from observations during the past few decades [29,34,37]. However, a model to comprehend the genesis of reservoir-triggered earthquakes has remained elusive likely due to lack of direct observations from the near-field of earthquakes.…”
Section: Introductionmentioning
confidence: 99%
“…2b) have shown that paleotopographic undulations of the magnitude of more than 200 m are encountered at several locations (Jain et al, 1995;Kale et al, 2014). The Trap-basement contact shows an elevation difference of almost 600 m within a linear distance of about 20 km across the WGE in deep drilling in the KWSZ (Gupta et al, 2017). Some of the chemostratigraphic formations of the Deccan Traps are of lesser thickness (see: Fig.1 in Schoene et al, 2015) than the amplitudes of the paleotopographic undulation of the basement.…”
Section: Deccan Basementmentioning
confidence: 97%
“…Geological and geophysical studies (Deshmukh and Sehgal, 1988;Peshwa and Kale, 1997;Raval and Veeraswamy, 2011) in subsequent years brought out the possibility of post-Trappean deformation along the Kurduwadi Lineament (KLZ), Pranhita-Godavari Rift zone (PGRZ) and the Koyna -Warna Seismic Zone (KWSZ). The KWSZ that has suffered sustained low-intensity seismicity for over 50 years (Gupta et al, 2017) is located along the Chiplun -Koyna Lineament. The deep crustal nature of these regional block boundaries has been validated by geophysical studies (e.g.…”
Section: Are Marked For Reference Detached Exposures (Marked By Starmentioning
confidence: 99%
See 1 more Smart Citation